Protein-Noble Gas Interactions Investigated by Crystallography on Three Enzymes - Implication on Anesthesia and Neuroprotection Mechanisms - Colloc’h, Nathalie; Marassio, Guillaume; Prange, Thierry (IntechOpen, 2011)
None